Implementation of E-Government Through Public Service Innovation in Sinjai Regency - Asdar Palewai; Umar Congge; Mochamad Nurdin (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2026)
This study aims to explore the implementation of e-government through public service innovation in Sinjai Regency. Digital transformation is crucial in public services to improve the efficiency, transparency, and accountability of local governments. The research method used is a qualitative approach with an explanatory type. The novelty of this study lies in a comprehensive analysis using six determinant indicators—communication infrastructure, connectivity and IT use, human resources, budget, legal instruments, and paradigm shifts—to dissect the complexity of digitalization at the local government level. The results show that e-government implementation in Sinjai Regency has been realized through various application innovations such as SIPPADAI, SIMPELMI, and SIPAKAINGE. Despite being supported by Regent Regulation Number 48 of 2023 and the commitment of regional leaders, its implementation still faces significant obstacles such as limited ICT infrastructure, low digital literacy, budget constraints, and resistance to digital paradigm shifts among employees. This study provides practical and theoretical contributions as an in-depth evaluation instrument for the implementation of the Electronic-Based Government System (SPBE) at the district level, while also serving as a strategic reference in mapping the structural barriers to digital transformation in the region.